A novel thermal reflow method for the fabrication of microlenses with an ultrahigh focal number. Issue 44 (16th May 2015) - Wang, M.; Yu, W.; Wang, T.; Han, X.; Gu, Erdan; Li, X.
<x xml:space="preserve">Abstract</x> A novel thermal reflow method for the monolithic fabrication of microlens arrays with ultrahigh focal numbers and tunable lens profiles.